2002
DOI: 10.1038/sj.sc.3101380
|View full text |Cite
|
Sign up to set email alerts
|

Significance of low compliance bladder in cauda equina injury

Abstract: Study design: Prospective investigation using serial urodynamic studies. Objective: To evaluate type of neurogenic bladder and to observe changes of autonomous detrusor contraction (ADC) after the normalization of the compliance and capacity of the bladder in cauda equina injury. Setting: Spinal Cord Injury Unit, Yonsei Rehabilitation Hospital, Seoul, Korea. Methods: Urodynamic studies were performed in 50 patients with complete cauda equina injury from trauma with an infusion ratio of 30 ml/min. Findings of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
0
11
0
2
Order By: Relevance
“…Literatürde, OY'li hastalarda nörojenik mesane tipi ile ilişkili faktörlerin değerlendirildiği çalışma sayısı az olup, veriler sonuçlarımız ile uyumludur (26 arasında pozitif korelasyon olduğu saptanmış olup, daha önceki çalışma sonuçları ile uyumlu bulunmuştur (26). Aynı çalışmada, düşük mesane kompliyansı olan grupta MCC'nin daha düşük olduğu da bildirilmiştir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Literatürde, OY'li hastalarda nörojenik mesane tipi ile ilişkili faktörlerin değerlendirildiği çalışma sayısı az olup, veriler sonuçlarımız ile uyumludur (26 arasında pozitif korelasyon olduğu saptanmış olup, daha önceki çalışma sonuçları ile uyumlu bulunmuştur (26). Aynı çalışmada, düşük mesane kompliyansı olan grupta MCC'nin daha düşük olduğu da bildirilmiştir.…”
Section: Discussionunclassified
“…Aynı çalışmada, düşük mesane kompliyansı olan grupta MCC'nin daha düşük olduğu da bildirilmiştir. Literatürde, OY'li hastalarda mesane boşaltım yöntemini etkileyen faktörleri değerlendiren çok az çalışma mevcuttur (8,26,27). Rapidi Kay nak lar…”
Section: Discussionunclassified
“…1 This study demonstrated that not all patients with discomplete SCIs accepted the use of sensation-dependent bladder emptying. However, the use of sensation-dependent bladder emptying will be determined based on the results of urodynamic studies if patients with discomplete SCIs express the desire to void.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also revealed that voiding dysfunction depends on the level of cord injury [19] . Furthermore, a prospective study demonstrated the association of cauda equina injury with low compliance of the bladder [20] . The present study showed that there was a close relationship between LUTS and cauda equina symptoms.…”
Section: Commentmentioning
confidence: 99%